IMPACT OF ORAL HYGIENE INTERVENTIONS ON STROKE PATIENTS: RAPID REVIEW - Eriyani, Theresia; Shalahuddin, Iwan; Pebrianti, Sandra; Maulana, Indra (Universitas Aisyah Pringsewu, 2023)
Background:Stroke can occur when there is an obstruction to the blood supply to the brain or when there is bleeding in a blood vessel in the brain. Stroke results in decreased neurological function, with clinical consequences depending on the degree of neurological damage. Post-stroke health problems may be exacerbated by poor oral hygiene. Poor oral hygiene results in the accumulation of bacteria in the oral cavity which allows these bacteria to enter the trachea. The purpose of this study was to determine the various oral hygiene interventions that can be carried out and their impact on the health status of stroke patients. Methods: This study uses a rapid review system where after obtaining articles from four databases, articles will be selected and assessed based on inclusion criteria, then a feasibility evaluation is carried out using The Joanna Briggs Institute (JBI) Critical Appraisal Tools. Results: After searching and analyzing, there were 6 articles that were judged to meet the criteria. From these 6 articles, there are 6 oral hygiene interventions that can be performed on stroke patients. Conclusion: The six interventions can have an effect on oral health status such as decreasing PI, GI, Candida colonization, oral hygiene, bleeding gums and preventing the occurrence of SAP (Stroke-Associated Pneumonia)